1977
DOI: 10.1111/j.1540-4560.1977.tb02012.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Requirements for Research on Human Sexual Behavior: From the Perspective of Participating Subjects

Abstract: This study utilized procedures representative of published research on human sexual behavior as a means of establishing a direct approach (via a postexperimental questionnaire) to generalizing about ethical standards for this area of investigation. The 40 males and 40 females who volunteered (as part of their introductory psychology requirement) to participate anonymously in this investigation completed a questionnaire about past sexual experiences and a personality measure of sexual attitudes, read an erotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Abramson, & Gottesdiener, 1975). Subjects were infromed that participation was both voluntary and annonymous (Abramson, 1977). Upon completion of the Mosher Sex Guilt scale, subjects were explained the nature of the study and asked if they had any additional questions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abramson, & Gottesdiener, 1975). Subjects were infromed that participation was both voluntary and annonymous (Abramson, 1977). Upon completion of the Mosher Sex Guilt scale, subjects were explained the nature of the study and asked if they had any additional questions.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, sex guilt was chosen because of the availability of a psychometrically sound sex guilt scale (Mosher, 1966(Mosher, , 1979 which was deemed inoffensive to both elderly and Asian populations. Incidently, our tendency to favor a personality measure over a behavioral measure also reflects this ethical consideration (Abramson, 1977).…”
mentioning
confidence: 96%
“…Abramson (1977) conducted a study involving 40 men and 40 women from an introductory psychology subject pool. Participation was extensive and involved completing an anonymous questionnaire regarding sexual experiences and attitudes, reading an erotic story and rating one's subsequent sexual arousal, being secretly observed in a waiting room containing sexually explicit magazines, responding to double-entendre words, and being tested for retention of information presented on reproductive biology.…”
mentioning
confidence: 99%
“…Ring et al (1970) have suggested that a detailed, personally orientated debriefing is sufficient to alleviate residual tension concerning experimental procedures as well as to induce a positive regard for the experiment and the subject's role in it. Abramson (1977) found that participants in a study considered debriefing should be an integral part of participation in psychology experiments. Should the investigator be in researcher or therapist mode when conducting the debriefing session?…”
Section: Debriefingmentioning
confidence: 98%
“…There are many different reasons. Some university courses require students to participate as volunteers in studies (Abramson, 1977) or are compensated with extra course credit for their participation (Stock & Geer, 1982). Although it is desirable for trainee professionals to experience what it is like to be a volunteer in a study, the ethics of this are questionable, as the exercise amounts to coercion.…”
Section: Recruitment To Studiesmentioning
confidence: 99%